The Impact of Agricultural Extension Services on Farm Output: A Worldwide Viewpoint - Kalogiannidis, Stavros; Syndoukas, Dimitrios (Research on World Agricultural Economy, 2024)
In order to increase farm productivity and sustainability on a worldwide scale, agricultural extension services are essential in bridging the gap between research and actual farming. This study examined agricultural extension services and their effects on farm productivity. Data were collected using a questionnaire from 382 professional farmers. The results show that agricultural workshops and training positively affect farm productivity, access to government demonstration farms positively influences farm productivity, and media-based agricultural programs have a positive effect on farm productivity. Workshops and training in agriculture may have a very favorable impact on farm output. It’s important to remember that the success of agricultural workshops and training might vary depending on a number of variables, including the training's quality, the information's applicability to local circumstances, the farmers' readiness to embrace new techniques, and the post-training assistance offered. In order to increase and facilitate access to knowledge, suitable production methods, and better inputs, the findings highlight the need to strengthen farmers' organizations and last-mile agricultural input providers. Farmers must have access to knowledge about marketing and other support services that are essential for agricultural growth in order to enhance global development in order to achieve greater farm productivity.